Informational Approach and Transformational Approach in Cross-cultural Advertising - Tran, Hoang My (2018)
This research address one of the most debatable subject of cross-cultural advertising, which is how multinational corporations choose between maintaining one approach and diversifying the methods of advertising when introducing their products to different overseas markets. The comparative analysis was conducted based on the criteria to which advertisements are different in the way they are either informational (logic-oriented) or transformational (emotion-oriented). Through the comparison of the informational versus transformational orientation in the advertisements from several multinational brands, the study notes whether MNEs alter their advertising approach in different host countries. The study commences with an analysis of 81 advertisement samples to observe the trend of MNEs advertising technique on the recent years. The result has indicated a great diversity, as several MNEs has chosen to standardize their methods, i.e. maintain one set of informational or transformational approach in different host countries markets. However, some MNEs (PepsiCo and Apple in this case) shows clear evidence in how their advertisements shift from being informational in the UK’s and France’s markets to being transformational in the China’s and Japan’s market. To address the question of the necessity to diversify the approach in cross-cultural context, the study continues with an experiment involving several participants from different national backgrounds, to test their reaction to the informational and transformational appeals in advertisements. The result of this experiments has drawn a clear pattern that consumers from dissimilar nationalities have different tastes and preferences. Whereas the participants with backgrounds from China shows compatibility to the transformational appeals, the participants from the UK tend to respond strongly to the informational appeals.